Pharmacovigilance and incidence of adverse drug reactions in hospitalized pediatric patients: a mini systematic review - Zakir Khan; Khayal Muhammad; Yusuf Karatas; Cagri Bilen; Farman Ullah Khan; Faiz Ullah Khan (SpringerOpen, 2020)
Abstract Background Pharmacovigilance is an identifying and responding process against an adverse drug reaction (ADRs) problem encountered in the drug administration. ADRs are among the common reasons for morbidity and fatality in pediatrics throughout the globe. Main body A systemic review of the previous 10 years (2010-2019) published studies were taken into consideration to describe observational studies on ADRs and to determine the incidence and characteristics of ADRs in pediatrics. Electronic relevant literature was searched in PMC, PubMed, Google Scholar, and OvidSP databases using MESH heading and text words. The titles, text, and abstracts were checked for patients below 18 years of age, nature of ADRs, observational studies (prospective or retrospective), and maximum information was recorded to count their frequency. The studies which discussed specific or particular drug exposures were not selected in this review. Of the 36,689 titles retrieved, 27 studies were selected for full-text review. Ten observational studies were added in the final review. Observational studies on pediatric were carried out in seven distinct nations. The predominant study design within observational methodological studies was prospective (n = 5, 50%). The overall average occurrence of ADRs incidence was 9.52%. ADRs reporting in male patients (54.6%) were more than females (45.4%). The severe types of ADRs were reported in four studies. Anti-microbials were the most common class of drugs related to ADRs. Conclusion This systematic review reveals that ADRs in pediatrics are serious public health problems. Periodic drug surveillance studies are mandatory for the safe and appropriate usage of medicines in pediatrics.